2014
DOI: 10.1038/nmeth.2784
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule evaluation of fluorescent protein photoactivation efficiency using an in vivo nanotemplate

Abstract: Photoswitchable fluorescent probes are central to localization-based super-resolution microscopy. Among these probes, fluorescent proteins are appealing because they are genetically encoded. Moreover, the ability to achieve a one to one labeling ratio between the fluorescent protein and the protein of interest makes them attractive for quantitative single molecule counting. The percentage of fluorescent protein that is photoactivated into a fluorescently detectable form (i.e. photoactivation efficiency) plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
317
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(335 citation statements)
references
References 43 publications
16
317
1
1
Order By: Relevance
“…The actual number of needle complexes, however, is likely to be higher as some clusters may be away from the focal plane and may escape detection. In addition, cluster detection would require the imaging of a minimum number of photon-switching events (five in our case), and although there are 24 mEos3.2-PrgH molecules in each needle complex that could be potentially imaged, it is likely that some needle complexes may not reach the minimum detection threshold because it has been reported that only 42% of mEos3.2 can be photoactivated to a fluorescently detectable form (44).…”
Section: Resultsmentioning
confidence: 99%
“…The actual number of needle complexes, however, is likely to be higher as some clusters may be away from the focal plane and may escape detection. In addition, cluster detection would require the imaging of a minimum number of photon-switching events (five in our case), and although there are 24 mEos3.2-PrgH molecules in each needle complex that could be potentially imaged, it is likely that some needle complexes may not reach the minimum detection threshold because it has been reported that only 42% of mEos3.2 can be photoactivated to a fluorescently detectable form (44).…”
Section: Resultsmentioning
confidence: 99%
“…The number of switching cycles is another important parameter to consider. For quantifying the stoichiometry of the target proteins, it is desirable to have PAFPs that can be switched on only once, although almost all PAFPs tend to blink more than once (31). However, for mapping of protein spatial organization, a larger number of switching cycles per molecule would allow the target structure to be sampled more times, which is advantageous when it comes to time-lapsed imaging for probing dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…This accounted for repeated emission and potential short-term blinking, but not potential long-term blinking, which was, however, expected to be minimal for PAmCherry and PAGFP (Durisic et al, 2014). This analysis was able to eliminate localization multi-appearances as evident from the pair-correlation function (Puchner et al, 2013) (Fig.…”
Section: Palm Image Analysismentioning
confidence: 99%